2018
DOI: 10.3389/fgene.2018.00143
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Oocyte-Manipulation, Zygote-Manipulation, and Genome-Reprogramming Effects on the Transcriptomes of Bovine Blastocysts

Abstract: Somatic cell nuclear transfer (scNT) embryos suffer from damage caused by micro-operation (manipulation) and inefficient genome reprograming that hinder their normal development at different levels and in distinct ways. These two effects are inseparable in the nature of the scNT embryo, although methods to separately measure them are needed to improve scNT technology and evaluate incoming reprogramming tools. As an attempt to meet these demands, we made bovine sham nuclear-transfer (shNT) blastocysts, special … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Genomic DNAs (gDNAs) were extracted from the tissue samples using DNeasy Blood & Tissue Kit (Qiagen) according to the manufacturer's instruction. Genomic DNAs obtained from three mice of the same ages were pooled before sonication using Bioruptor Pico (Diagenode) and purified using with AMPure XP beads (Beckman) (Min, Park, & Kang, ). For preparation of MBD capture, 7 μl MBD‐Biotin proteins per sample from MethylMiner Methylated DNA Enrichment Kit (Thermo) was first incubated with 10 μl of precleared Dynabeads (Thermo) at RT for 1 hr.…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNAs (gDNAs) were extracted from the tissue samples using DNeasy Blood & Tissue Kit (Qiagen) according to the manufacturer's instruction. Genomic DNAs obtained from three mice of the same ages were pooled before sonication using Bioruptor Pico (Diagenode) and purified using with AMPure XP beads (Beckman) (Min, Park, & Kang, ). For preparation of MBD capture, 7 μl MBD‐Biotin proteins per sample from MethylMiner Methylated DNA Enrichment Kit (Thermo) was first incubated with 10 μl of precleared Dynabeads (Thermo) at RT for 1 hr.…”
Section: Methodsmentioning
confidence: 99%
“…Bioinformatics analysis of the sperm proteome suggested that abnormalities in cytoskeleton and nuclear reprogramming might be related to the deletion of sperm proteins. Cloned embryos had higher reactive oxygen species (ROS) levels, higher endoplasmic reticulum stress, and embryo activation block [23–25]. Here, we also found many sperm proteins enriched in ROS‐related processes, enzyme activity regulation, unfolded protein binding, and ion binding, which suggests that the higher stress state of cloned embryos might be related to the absence of sperm proteins.…”
Section: Discussionmentioning
confidence: 90%
“…The genetic nature of a mutation, such as whether it is in or out of frame or is a missense or a non-sense mutation, is not considered by the equation, although it is unambiguously useful to include such genetic aspects of an indel in the calculation to permit assessment of the severity of the mutation in relation to molecular and biochemical function. However, PCR and sequencing errors are not rare, and the error rate may increase greatly when samples containing limited amounts of genomic material, such as early embryos, are used (Min et al, 2017, 2018a). We indeed observed single base-pair insertions, deletions, and substitutions that randomly appeared among the amplicon reads, and we excluded these uncertain single-nucleotide variations (SNVs) from the ID calculation.…”
Section: Discussionmentioning
confidence: 99%
“…Successful mating was determined the following morning by detection of a vaginal plug. Mouse zygotes were transferred to M2 medium (Sigma) containing 0.1% (w/v) hyaluronidase to remove cumulus cells and cultured in M16 medium (Sigma) at 37°C, 5% CO 2 in air (Min et al, 2018a).…”
Section: Methodsmentioning
confidence: 99%